Intelligent image-based deformation-assisted cell sorting with molecular specificity - Nawaz, Ahmad Ahsan; Urbanska, Marta; Herbig, Maik; Noetzel, Martin; Kraeter, Martin; Rosendahl, Philipp; Herold, Christoph; Toepfner, Nicole; Kubankova, Marketa; Goswami, Ruchi; Abuhattum, Shada; Reichel, Felix; et al. (Nature Methods, 2020)
Although label-free cell sorting is desirable for providing pristine cells for further analysis or use, current approaches lack molecular specificity and speed. Here, we combine real-time fluorescence and deformability cytometry with sorting based on standing surface acoustic waves and transfer molecular specificity to image-based sorting using an efficient deep neural network. In addition to general performance, we demonstrate the utility of this method by sorting neutrophils from whole blood without labels.
CRIS-Team Scopus Importer:2022-08-05